The demons of liberal democracy - Pabst, Adrian (Polity Press, 2019)
"In this book, Adrian Pabst contends that liberal democracy is undemocratic: intolerant about the values of ordinary people while concentrating power in the hands of elites. In order to banish liberal democracy's demons, he proposes ideas for economic democracy, a politics of persuasion and a balance of personal freedom with social solidarity"--